Understanding the determinants of learner engagement in MOOCs: An adaptive structuration perspective - Sun, Yongqiang; Guo, Yanping; Zhao, Yiming (Computers and education, 2020)
As an innovative educational paradigm, the massive open online course (MOOC) has received extensive attention from both academia and industry. Extant literature has made much effort to investigate the technological supports of MOOCs but how learners understand and master these technologies is still unclear. Moreover, given the collaborative features (e.g. discussion forum and peer assessment) of MOOCs, it is vital to ascertain the mechanism through which group learners reach a consensus on the technology usage and thereby engage in MOOCs. To advance this line of research, the study proposes a theoretical model leveraging adaptive structuration theory. Specifically, we identify three contextualized factors (i.e., collaborative spirit, task interdependence, and social interaction ties) as the antecedents of consensus of appropriation. Through an online survey recruiting 374 Chinese University MOOC learners, this study demonstrates that collaborative spirit, task interdependence and social interaction ties are positively related to consensus of appropriation, which will facilitate commitment and learner engagement. In addition, commitment is also confirmed to enhance learner engagement. Implications and limitations are further discussed. •Viewing learner engagement in MOOCs from an adaptive structuration perspective.•Consensus of appropriation plays an important role in MOOCs.•Identifying three contextualized features related to consensus of appropriation.